1995
DOI: 10.1074/jbc.270.17.9770
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Action of the High Affinity Calcium Binding Sites in Skeletal Muscle Troponin C

Abstract: Mutants of each of the four divalent cation binding sites of chicken skeletal muscle troponin C (TnC) were constructed using site-directed mutagenesis to convert Asp to Ala at the first coordinating position in each site. With a view to evaluating the importance of site-site interactions both within and between the N- and C-terminal domains, in this study the mutants are examined for their ability to associate with other components of the troponin-tropomyosin regulatory complex and to regulate thin filaments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 59 publications
5
36
2
3
Order By: Relevance
“…As demonstrated by Gagné et al (26) and in the present 2 Gagné et al (26) on the other hand have concluded, based on their NMR structure, that Val 65 , positioned at the C-terminal end of helix C and immediately adjunct to loop II, is the pivot point associated with site II. Houdusse et al (14), based on their structural analyses of the rabbit crystals, have identified small and larger hinge regions for each of EF-hands I and II The small regions involve residues at the Cterminal ends of helices A and C. study, the substitution of Glu 41 by Ala also impairs the closed to open structural transition as well as functionality (31) as assessed by tension measurements in the skinned muscle fiber system.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As demonstrated by Gagné et al (26) and in the present 2 Gagné et al (26) on the other hand have concluded, based on their NMR structure, that Val 65 , positioned at the C-terminal end of helix C and immediately adjunct to loop II, is the pivot point associated with site II. Houdusse et al (14), based on their structural analyses of the rabbit crystals, have identified small and larger hinge regions for each of EF-hands I and II The small regions involve residues at the Cterminal ends of helices A and C. study, the substitution of Glu 41 by Ala also impairs the closed to open structural transition as well as functionality (31) as assessed by tension measurements in the skinned muscle fiber system.…”
Section: Discussionsupporting
confidence: 53%
“…The effects of mutating other liganding residues in sites I and II of sTnC on its Ca 2ϩ binding and functional properties have been previously reported (31,(63)(64)(65)(66)(67)(68). These have been largely concerned with loop position 1 and/or 3 and include in loop I the mutations D30V and D30A (position 1) and D32G and D32A (position 3).…”
Section: Discussionmentioning
confidence: 99%
“…The two C-terminal high-affinity Ca 2+ -binding domains (EF3 and EF4) are functional in all cardiac and skeletal TnC isoforms. These two high-affinity Ca 2+ -binding sites are believed to be fully occupied by either Ca 2+ or Mg 2+ , depending on the physiological conditions of the muscle, and are likely to play a structural role providing stability to the Tn complex (25)(26)(27). The TnC-based Ca 2+ regulation of contraction appears to have separate mechanisms in skeletal vs. cardiac muscles.…”
Section: Troponin Cmentioning
confidence: 99%
“…, as demonstrated by 45 Atopic allergies, which comprise a wide range of IgE-mediated disorders such as hay fever, asthma, atopic dermatitis, and food allergies, affect 12-20% of the population. Pollen originating from trees, grasses, and weeds are among the most important sources of airborne allergens and are associated with seasonal patterns of allergic diseases.…”
mentioning
confidence: 99%